Influence of corona treatment specific energy on wettability of polyolefine filled film - Żenkiewicz, M. (Polimery, 2022)
Effect of specific energy of treatment (Ej) by corona discharge on changes of contact angle of the film (based on PE-HD/PP-i blend) containing mineral fillers (Table 1, Fig. 2-4) were presented. Contact angles with water (W), glycerol (G), formamide (F) or diiodomethane (D) were investigated. Surface free energy (SEP) has been calculated using either Owens-Wendt's method (OW) or by contact angle hysteresis one (HKZ). The biggest changes of this energy take place in the range of specific energy of treatment up to 1.5 kJ/m2 (Table 3). Polar interactions are most important for an increase in interface interaction film/measure liquid while dispersion interactions, occurring in case of D, are of less importance. Comparison of the results of calculations made using OW or HKZ methods show the possibility to use the latter one for calculation of SEP value of the activated film. From the results it is clear that the fastest decay of filled film activation effects, i.e. contact angle changes, takes place during first two days after activation. After 7 days the changes become insignificant.